KAJIAN INDOOR HEALTH AND COMFORT PADA RUANG KELAS SDN GROGOL SELATAN 09 PAGI - Rifa Nur Habibah; Yeptadian Sari (RUSTIC, 2024)
The classroom is a room used for teaching and learning activities. These rooms tend to be crowded, occupied by a number of active students and teachers, making it possible for disease transmission to occur if the classrooms are uncomfortable and do not meet health standards. Because various factors can influence the success of teaching and learning activities, it is important to have classrooms that meet health and comfort standards. This research will focus on classes at elementary school level, with the research object being SDN Grogol Selatan 09 Pagi which is located in South Jakarta. The research method used is descriptive qualitative by conducting field observations and literature analysis. The aim of this research is to determine the quality of Indoor Health and Comfort (IHC) in the classrooms of SDN Grogol Selatan 09 Pagi in order to create an optimal learning environment. The research results show that five of the eight points of Indoor Health and Comfort criteria have been met, namely outdoor air introduction, chemical pollutants, visual comfort, thermal comfort, and acoustic levels.